2020
DOI: 10.3390/nu12020338
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Reactivation During Lactation: Impact of Antibody Kinetics and Neutralization in Blood and Breast Milk

Abstract: Human cytomegalovirus (HCMV) is shed into breast milk in nearly every seropositive woman during lactation. This reactivation shows mostly a self-limited, unimodal course. The dynamics and functional role of HCMV-specific-IgG in breast milk and in plasma during reactivation are unknown. Milk whey viral loads were monitored with real-time PCR in 18 HCMV-seropositive mothers over two months postpartum. HCMV-antibody binding assays (ECLIA) and antigen-specific immunoblotting were performed from plasma and correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…As HCMV reactivates strictly locally in the mammary glands during lactation and none of the women showed signs of systemic HCMV reactivation with DNAemia, strain composition and diversity among different compartments (blood and mammary glands) could not be analyzed (Lazar et al, 2020). Local reactivation during lactation is thought to be triggered by invasion of CD14+ monocytes (one site of HCMV latency) into the mammary glands (Maschmann et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As HCMV reactivates strictly locally in the mammary glands during lactation and none of the women showed signs of systemic HCMV reactivation with DNAemia, strain composition and diversity among different compartments (blood and mammary glands) could not be analyzed (Lazar et al, 2020). Local reactivation during lactation is thought to be triggered by invasion of CD14+ monocytes (one site of HCMV latency) into the mammary glands (Maschmann et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…BM samples originated from the BlooMil study (Lazar et al, 2020;Rabe et al, 2020) and were analyzed in collaboration with the Department of Neonatology at the University Children's Hospital, Tuebingen. Samples (~80 ml) from HCMVseropositive mothers of mostly preterm infants were collected within four defined time periods: 10-15, 25-30, 40-45 and 55-60 days postpartum (T1-T4).…”
Section: Cohort and Bm Specimensmentioning
confidence: 99%
See 2 more Smart Citations
“…Virus neutralization assays demonstrated substantially higher values in plasma compared to whey at 2 months postpartum. No newborn transmission correlates were provided, but the authors concluded that, during reactivation in the post‐partum period, CMV‐specific‐IgG reactivities and neutralizing capacities are much lower in whey than in plasma 32 . These findings suggest that any beneficial effect of maternal antibody on modulating breast milk‐associated transmission may be mediated by protection against infection in the systemic, not mucosal, compartment.…”
Section: Breast Milk‐acquired Post‐natal CMV Infectionsmentioning
confidence: 99%